Population Ecology and Lecturer Performance: The Roles of Culture, LMX, Commitment, and OCB - Wibowo, Hermansyah Andi; Fatah, Abdul (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study examines the relationships among perceived organizational culture, leader–member exchange (LMX), organizational commitment, organizational citizenship behavior (OCB), and lecturers’ performance in Indonesian higher education. It contributes to population ecology theory by reframing inertia as an individual-level perceptual and relational mechanism under regulatory pressure rather than a firm-level survival outcome. Drawing on the population ecology perspective, the study treats organizational stability and adaptation as contextual forces shaped by coercive regulations that structure routines and norms. Using cross-sectional data and covariance-based structural equation modeling (CB-SEM; N = 240), the findings show that perceived organizational culture positively influences LMX, organizational commitment, and OCB, which in turn enhance lecturer performance. The results demonstrate how individual adaptive behaviors reflect the inertia–adaptation balance within regulated academic systems. Practically, the study informs university leaders on leveraging culture and leader–member relations to sustain lecturer performance amid regulatory constraints.